2009
DOI: 10.15517/rbt.v58i4.5423
|View full text |Cite
|
Sign up to set email alerts
|

Centrocestus formosanus (Opisthorchiida: Heterophyidae) como causa de muerte de alevines de tilapia gris Oreochromis niloticus (Perciforme: Cichlidae) en el Pacífico seco de Costa Rica

Abstract: Centrocestus formosanus (Opisthorchiida: Heterophyidae) as a cause of death in gray tilapia fry Oreochromis niloticus (Perciforme: Cichlidae) in the dry Pacific of Costa Rica. Centrocestus formosanus is a zoonotic trematode from Asia and has been mainly associated as cause of death of cultured fish. To identify pathogen trematode species in tilapia fry (Oreochromis niloticus) and to determine mollusks hosting these parasites, freshwater mollusks were collected from tilapia cultured ponds and experimental infec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…In Costa Rica there are few studies to know the parasitic biodiversity that affects tilapia fish (Arguedas et al, 2010). This study is the first report for identification of parasite diversity on tilapia fish larvae under systems culture, in stage reversal sexual process, in which parasitic agents can cause high mortalities, or immunosuppressive (Conroy, 2005;Pádua, Ishikawa, Ventura, Martins, & Tavares, 2013).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In Costa Rica there are few studies to know the parasitic biodiversity that affects tilapia fish (Arguedas et al, 2010). This study is the first report for identification of parasite diversity on tilapia fish larvae under systems culture, in stage reversal sexual process, in which parasitic agents can cause high mortalities, or immunosuppressive (Conroy, 2005;Pádua, Ishikawa, Ventura, Martins, & Tavares, 2013).…”
Section: Discussionmentioning
confidence: 93%
“…A digenean trematode Centrocestus formosanus was reported as the cause of death of tilapia fingerlings in the dry Pacific of Costa Rica (Arguedas, Dolz, Romero, Jiménez & León, 2010) determining experimentally part of helminth life cycle; although, there are no similar studies in Costa Rica. About wild fish, exists only an investigation (Sandlund, Daverdin, Choudhury, Brooks & Diserud, 2010), but findings remained at the project report level.…”
mentioning
confidence: 99%
“…In these hosts, metacercariae are formed on the gill arches and filaments, causing pathological alterations such as cartilage proliferation and inflammatory reaction around the cyst (MITCHELL et al, 2000). Depending on factors such as worm burden, infection by C. formosanus can lead to reduced respiratory capacity and even fish mortality, thus resulting in potential damage to fish farming (MITCHELL et al, 2005;ARGUEDAS-CORTÉS et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The life cycle of C. formosanus was firstly elucidated in Asia (CHEN, 1942), and since then, experimental infection studies involving this parasite have been conducted in at least 12 countries (PINTO; MELO, 2011 (HERNÁNDEZ et al, 2003) and Costa Rica (ARGUEDAS-CORTÉS et al, 2010). Recently, Pinto and Melo (2010) observed that the invasive snail Melanoides tuberculata (Müller, 1774) was involved in the transmission of C. formosanus in Brazil.…”
Section: Introductionmentioning
confidence: 99%
“…Vogelbein & Overstreet (1988) noted that C. formosanus induces an inflammatory response characterized by an unusual proliferation of fibroblasts, forming a continuous encapsulation around the parasite, which eventually destroys the gill tissue. Arguedas-Cortés et al (2010), in an effort to identify the species of trematode pathogens for tilapia fry in Costa Rica, made the first records of the presence of metacercariae of C. formosanus . These authors reported intensities of between 1018 and 1027 metacercariae per parasitized fish in experimental infections, and a high fry mortality.…”
Section: Tilapiamentioning
confidence: 99%